Mechanisms of observed spatial heterogeneity in rainfall variability over the winter rainfall zone of South Africa - Conradie, Willem (Department of Environmental and Geographical Science, 2025)
Renewed interest in South Africa's Winter Rainfall Zone (WRZ) has emerged in the wake of the 2015–2017 “Day Zero” drought and water crisis. However, this has yielded little insight into the spatial heterogeneity in WRZ climatological seasonality and rainfall variability or their drivers, despite such understanding being crucial for interpreting past and robustly projecting future climate change patterns. Hence, the spatial heterogeneity of WRZ rainfall is investigated in relation to regional rainfall systems and hemispheric climate drivers, using both gauge-based and gridded data. A novel rainfall data quality control and gap-filling procedure involving Generalised Additive Models for Location, Scale and Shape (GAMLSS) is developed to obtain a continuous, high-density 41-year gauge-based rainfall dataset for the WRZ and its immediate surroundings. The effectiveness of this procedure in detecting common errors and accurately in-filling missing values is demonstrated. Hierarchical cluster analysis on these data is used to identify the WRZ and investigate its substructure. A uniform core WRZ is identified between the meridional Cape Fold Belt and west coast. Over the WRZ, strong spatial coherence between temporal variability patterns and seasonality is found. In places, the transition to the surrounding all-year and late summer rainfall zones is highly complex. Spatial heterogeneity in rainfall seasonality and variability is closely related to heterogeneity in the dominant rain-bearing winds and mid-tropospheric synoptic states. Throughout the year, the WRZ core receives more than 70% of its rainfall from westerly disturbances. In contrast, even during winter, the coastal all-year rainfall zone receives less than half its rainfall under dominant westerly or north-westerly synoptic flows. Correlations of rainfall timeseries between these zones is insubstantial. This demonstrates that the all-year rainfall zone represents a distinct climatic zone in its own right, rather than a superposition of summer and winter rainfall influences. Spatial heterogeneity in wind direction-rainfall relationships explain much of the heterogeneity in the evolution of Day Zero drought severity. The drought footprint expanded north-eastward into the transitional and surrounding areas even as drought relieving rains occurred around Cape Town in 2018 and 2019. This rainfall recovery was associated with the early winter frequency of mid-latitude mid-tropospheric troughs—which bring rain primarily to the south-western corner of the domain—returning to near pre-drought levels. The Day Zero Drought, although unprecedented (in more than a century of records) in 3-year intensity, coincides with a spatially localised but coherent quasi-cyclic multi-decadal pattern of repeated severe multi-year droughts over the WRZ. This low-frequency variability is not mirrored in the surrounding rainfall zones or any other winter rainfall region of the Southern Hemisphere extra-tropics. This finding may indicate a prominent role for zonally asymmetric climate modes. Multi-decadal rainfall variability is most closely associated with recently documented multi-decadal variability in the south-west Indian and Atlantic Oceans. We confirm that over certain periods a significant correlation with some established modes of hemispheric and global variability is apparent for sub-regions of the WRZ. However, none of these modes are consistently and strongly associated with annual or winter semester rainfall variability across the WRZ. Protracted early winter WRZ droughts are associated with amplitude changes and phase-shifts in the quasi-stationary Southern subtropical and mid-latitude zonal wave-4 through frequency changes in WRZ rain-bearing synoptic systems. Evidence suggests that these zonal wave-4 phase shifts are partially forced by regional tropical and subtropical convection. This thesis demonstrates an approach to linking sub-regional rainfall heterogeneity to occurrence fre-quency of regional-scale weather systems. These frequencies, in turn, are associated with global and hemi-spheric modes of variability. It is proposed that this can be extended to support more robust understanding of the drivers of rainfall variability at decision-relevant scales.